Instrumentation and signal processing for the detection of Obstructive Sleep Apnea - Lee, Teck Hock. (2008)
In this thesis, we investigated the use of features derived from snoring sounds as a method of simplying the diagnosis procedure and to discriminate between benign (non-pathological) and apenic (OSA-related) episodes of snoring.